Purpose, processes, partnerships, and products: four Ps to advance participatory socio‐environmental modeling. Issue 1 (8th December 2017) - Gray, Steven; Voinov, Alexey; Paolisso, Michael; Jordan, Rebecca; BenDor, Todd; Bommel, Pierre; Glynn, Pierre; Hedelin, Beatrice; Hubacek, Klaus; Introne, Josh; Kolagani, Nagesh; Laursen, Bethany; et al.
Abstract: Including stakeholders in environmental model building and analysis is an increasingly popular approach to understanding ecological change. This is because stakeholders often hold valuable knowledge about socio‐environmental dynamics and collaborative forms of modeling produce important boundary objects used to collectively reason about environmental problems. Although the number of participatory modeling (PM) case studies and the number of researchers adopting these approaches has grown in recent years, the lack of standardized reporting and limited reproducibility have prevented PM's establishment and advancement as a cohesive field of study. We suggest a four‐dimensional framework (4P) that includes reporting on dimensions of (1) the Purpose for selecting a PM approach (the why ); (2) the Process by which the public was involved in model building or evaluation (the how ); (3) the Partnerships formed (the who ); and (4) the Products that resulted from these efforts (the what ). We highlight four case studies that use common PM software‐based approaches (fuzzy cognitive mapping, agent‐based modeling, system dynamics, and participatory geospatial modeling) to understand human–environment interactions and the consequences of ecological changes, including bushmeat hunting in Tanzania and Cameroon, agricultural production and deforestation in Zambia, and groundwater management in India. We demonstrate how standardizing communication about PM case studies can lead to innovation and new insights about model‐based reasoning in support of ecological policy development. We suggest that our 4P framework and reporting approach provides a way for new hypotheses to be identified and tested in the growing field of PM.